Robotic approach with neoadjuvant chemotherapy in adult Wilms’ tumor: A feasibility study report and a systematic review of the literature - Simone Sforza; Valeria Emma Palmieri; Maria Rosaria Raspollini; Giandomenico Roviello; Alberto Mantovani; Umberto Basso; Maria Carmen Affinita; Alberto D'Angelo; Lorenzo Antonuzzo; Marco Carini; Andrea Minervini; Lorenzo Masieri (Asian Journal of Urology)
Objective: The incidence of Wilms’ tumor (WT) among adult individuals accounts for less than 1% of kidney cancer cases, with a prognosis usually less favorable when compared to younger individuals and an overall survival rate of 70% for the adult patients versus 90% for the pediatric cases. The diagnosis and treatment of WT are complex in the preoperative setting; neoadjuvant chemotherapy (NAC) or robotic surgery has rarely been described. This study aimed to review the literature of robotic surgery in WT and report the first adult WT management using both NAC and robotic strategy. Methods: We reported a case of WT managed in a multidisciplinary setting. Furthermore, according to Preferred Reporting Items for Systematic reviews and Meta-Analyses recommendations, a systematic review of the literature until August 2020 of WT treated with a robotic approach was carried out. Results: A 33-year-old female had a diagnosis of WT. She was scheduled to NAC, and according to the clinical and radiological response to a robotic radical nephrectomy with aortic lymph nodes dissection, she was managed with no intraoperative rupture, a favorable surgical outcome, and a follow-up of 25 months, which did not show any recurrence. The systematic review identified a total number of 230 cases of minimally invasive surgery reported in the literature for WT. Of these, approximately 15 patients were carried out using robotic surgery in adolescents while none in adults. Moreover, NAC has not been administered before minimally invasive surgery in adults up until now. Conclusion: WT is a rare condition in adults with only a few cases treated with either NAC or minimally invasive approach so far. The advantage of NAC followed by the robotic approach could lead to favorable outcomes in this complex scenario. Notwithstanding, additional cases of adult WT need to be identified and investigated to improve the oncological outcome.